Land Surface Coverage, Main Vegetation and Physical Soil Characteristics of West Side of Lawu Mountain - Rahayu Rahayu; Puguh Karyanto (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2015)
Sustainability of catchment area management of a mountain requeres identification the vegetation and condition of the major vegetation. This reserachs purpouse was characterizing major vegetation, coverage and  soil properties at 1000 m elevation sea level to the top of Lawu mountain. Survey was started by identification of every vegetation unit followed by taking soil sample that was analyzed in laboratory for identifying the properties. Sampling and  identification  conducted close by common climbing track line to the top, including Jogorogo and Cemoro Sewu East Java, and Cemoro Kandang and Sukuh Central java. Coverage of vegetation  used  sattellite immage landsad and was analyzed  by  Arview software. Results showed that intens and dense forest was 36,22% and the other was rare density forest. Major vegetation of Lawu mountain was Pinus (Pinus merkusii), Cemara (Casuarina equisatifolia), Tanganan (Schleptera sp), Akasia gunung (Acasia decurren), rumput vestuca, Cantigi (Vaccinium sp) kayu pasang (Lithocarpus pruinusa)  and vegetables on agriculture land. Every type of vegetation unit had different soil physycal properties of topsoil, while elevation had effect on soil bulk volume and porocity.